Down‐regulation of the non‐coding RNA H19 and its derived miR‐675 is concomitant with up‐regulation of insulin‐like growth factor receptor type 1 during neural‐like differentiation of human bone marrow mesenchymal stem cells. (30th March 2018) - Farzi‐Molan, Asghar; Babashah, Sadegh; Bakhshinejad, Babak; Atashi, Amir; Fakhr Taha, Masoumeh
Abstract: The differentiation of human bone marrow mesenchymal stem cells (BMSCs) into specific lineages offers new opportunities to use the therapeutic efficiency of these pluripotent cells in regenerative medicine. Multiple lines of evidence have revealed that non‐coding RNAs play major roles in the differentiation of BMSCs into neural cells. Here, we applied a cocktail of neural inducing factors (NIFs) to differentiate BMSCs into neural‐like cells. Our data demonstrated that during neurogenic induction, BMSCs obtained a neuron‐like morphology. Also, the results of gene expression analysis by qRT‐PCR showed progressively increasing expression levels of neuron‐specific enolase (NSE) as well as microtubule‐associated protein 2 (MAP‐2) and immunocytochemical staining detected the expression of these neuron‐specific markers along differentiated BMSC bodies and cytoplasmic processes, confirming the differentiation of BMSCs into neuronal lineages. We also compared differences in the expression levels of the long non‐coding RNA (lncRNA) H19 and H19‐derived miR‐675 between undifferentiated and neurally differentiated BMSCs and found that during neural differentiation down‐regulation of the lncRNA H19/miR‐675 axis is concomitant with up‐regulation of insulin‐like growth factor type‐1 (IGF‐1R), a well‐established target of miR‐675 involved in neurogenesis. The findings of the current study provide support for the hypothesis that miR‐675 may confer functionality to H19, suggesting a key role for this miRNA in the neural differentiation of BSMCs. However, further investigation is required to gain deeper insights into the biological roles of this miRNA in the complex process of neurogenesis.